BUDAYA POPULER DALAM NOVEL KAMI (BUKAN) SARJANA KERTAS KARYA J.S. KHAIREN (SOSIOLOGI SASTRA) - Hendriyanto, Agoes; Hendriyansyah, Muhamad Devi; Setyowati, Eny (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2023)
This study aims to determine the form of popular culture of hedonism and materialism contained in the novel Kami (Not) Sarjana Kertas by J.S Khairen in terms of the sociology of literature. Qualitative research with the object of study is a novel with the title "We (Not) Paper Graduates" by J.S Khairen. The data collection method was obtained from the document technique with the text in the novel Kami (Not) Sarjana Kertas. The results of the study are as follows: First, popular culture in the form of hedonism consists of three forms, namely 1) prioritizing momentary pleasures; 2) contemporary lifestyle; and 3) the use of modern technology. Second, the popular culture of materialism consists of three, namely 1) the material possession of wealth; 2) activities that generate money; and 3) the assumption that money is everything.